Paul and the Torah - Gaston, Lloyd (Eugene, Oregon, Wipf & Stock Publishers, 2006)
Argues that the terms of Paul's mission must be taken seriously and that it is totally inappropriate to regard his "conversion" as a transition from one religion to another. Paul's congregations were not made up of Christian Jews: they were exclusively Gentile. He therefore focused on God's promises to Abraham concerning Gentiles which were fulfilled in the faithfulness of Jesus Christ. The inclusion of Gentiles in the elect people of God through their incorporation into Christ thus does not mean a displacement of Israel.
Paul and the Torah -- Angels and Gentiles in early Judaism and in Paul -- Abraham and the righteousness of God --
Includes bibliographical references (pages 191-239) and indexes.
Keywords: Bible. -- Theology; Law (Theology) -- Biblical teaching